Inverse PCR-based detection reveal novel mobile genetic elements and their associated genes in the human oral metagenome - Supathep Tansirichaiya; Endre Winje; Johannes Wigand; Mohammed Al-Haroni (BMC, 2022)
Abstract The human oral cavity is one of the hotspots harboring multiple mobile genetic elements (MGEs), which are segments of DNA that can move either within bacterial genomes or between bacterial cells that can facilitate the spreading of genetic materials, including antimicrobial resistance genes. It is, therefore, important to investigate genes associated with the MGEs as they have a high probability of dissemination within the bacterial population under selective pressure from human activities. As one-third of oral bacteria are not yet culturable in the laboratory condition, therefore, in this work, it is aimed to detect and identify the genetic contexts of MGEs in the oral cavity through an inverse PCR (IPCR)-based approach on the oral metagenomic. The human oral metagenome was extracted from saliva samples collected from healthy individuals in Tromsø, Norway. The extracted DNA was partially digested with the HindIII restriction enzyme and self-circularized by ligation. DNA primers targeting each MGE were designed to amplify outwards from the MGEs and used for the IPCR on the circularized DNA products. The IPCR amplicons were cloned into a pCR-XL-2-TOP vector, screened, and sequenced. Out of 40 IPCR amplicons, we confirmed and verified the genetic contexts of 11 samples amplified with primers targeting integron gene cassettes (GCs), IS431 composite transposons, and Tn916 conjugative transposons (tet(M) and xis-int). Novel integron GCs, MGEs, and variants of Tn916 conjugative transposons were identified, which is the first report using the IPCR technique to detect the genetic contexts of MGEs in the oral metagenomic DNA.